PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 007 PEMATANG IBUL KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Sri Hayati; Lazim.N Lazim.N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the low learning outcomes IPA students, with an average grade 68,83. While the value of the minimum completeness criteria (KKM) 75 is among the student who were 30people only students who reach KKM with classical completeness 50%. The research is a classroom action research (CAR) conducted aims to improve student learning outcomes IPA SD class country IV 007 Pematang Ibul by applying cooperative learning model numbered head together. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results of stidying the get average of the results of study before action increased 12,84% to 68,83 77,67% in cycle 1.in cycle II increased 17,20% be average grade 80,67%. Theacher’s activity on the cycle I meeting I by mean 55% enough category, on the cycle II meting II score result of the theacher’s activity by mean 62,50%. Next cycle II meeting I score result of the theacher’s activity by mean 87,50% good category. On the meeting II the research finding also having improved by mean 100% very good category. Engage analysis result students activitas in cycle I by mean 50,00% enough category in meeting II 57,50% in cycle the studentsunderstand the activitas cooperative learning numbered head together. In cycle II activity students scor 77,50% good category.IV class research results SDN 007 Pematang Ibul prove that the application cooperative learning numbered head together can improve learning outcomes IPA grade IV SDN 007 Pematang Ibul.Keywords. Cooperative Learning model numbered head together and achievement